Biochemical polymorphisms and genetic relationships between Brazilian and foreign breeds of pigs reared in Brazil - TAGLIARO, Claudia Helena (2011)
The genetic variability of 14 protein systems encoded by 15 structural loci was investigated in blood samples of Piau and Caruncho pig breeds. The results were compared with those obtained previously for samples of Landrace, Large White, Duroc and Mouro. The degree of genetic variability obtained for Piau (He=0.114) was similar to that estimated for other breeds reared in Brazil (Landrace, He=0.116; Large White, He=0.119; Duroc, 0.095; Mouro, He= 0.130). Caruncho showed the lowest variability (He= 0.056). The gene frequencies at the polymorphic loci were used to evaluate the usefulness of these systems for paternity testing and the combined probabilities of paternity exclusion were estimated at 58% for the Piau and 36% for the Caruncho breed. Analysis of genetic distances revealed that the greatest similarity observed was between Piau and Landrace (D=0.042). Caruncho showed the greatest divergence among all breeds compared and the distances between this breed and others range from 0.107 (with Landrace) to 0.176 (with Duroc). The tree constructed by UPGMA and Rogers Distance gave a topology in which Piau and Mouro joined with the European breeds (Landrace and Large White) whereas Caruncho was separated from all the other breeds. The results of the analysis of the Caruncho samples should be interpreted with caution since the number of animals studied was small.